Endoscopic ultrasound guided thrombin injection of angiographically occult pancreatitis associated visceral artery pseudoaneurysms: Case series - Gamanagatti, Shivanand (World J Gastrointest Endosc, 2015)
Pseudoaneurysm is a known complication of pancreatitis associated with significant mortality and morbidity. Imaging plays an important role in the diagnosis and management. Computed tomography (CT) helps localize the lesion and the severity of the background pancreatitis but digital subtraction angiography with coil embolization is recommended to avoid bleeding and inadvertent surgery. However, in cases where angiographic coil embolization is not feasible due to technical reasons, thrombin injection via CT or ultrasound guidance remains a viable option and often described in literature. In this series, effort has been made to highlight the role of endoscopic ultrasound guided thrombin instillation especially in patients with poorly visualized pseudoaneurysm on ultrasound thereby avoiding surgery and the associated mortality and morbidity.